PENINGKATAN LOYALITAS PELANGGAN MELALUI KEPANTASAN HARGA DAN PENANGANAN KOMPLAIN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Sudarti, Ken; susanti, rusni (LPPM STIE DHARMAPUTRA SEMARANG, 2011)
Business at beauty industrial more met at cities entire Indonesia. Willing woman class to beautify self and care beauty is phenomenon that support more the faster this business. Recently, beauty and body treatment is being topic that many discussion. So, the important beauty and body treatment for a part society this time, on that account many company beauty sells product or beauty service. Population in this watchfulness service user Natasha Skin Care at Semarang during year 2010. Result from this watchfulness has influence towards customer satisfaction, this seen from result t count > t table or significant < 0.05. Handling complain has influence towards customer satisfaction, this seen from result t count > t table or significant < 0,05. Has influence towards customer loyalty, this seen from result t count > t table or significant < 0.05. has influence towards customer loyalty, this seen from result t count > t table or significant < 0,05. Handling complain has influence towards customer loyalty, this seen from result t count > t table or significant < 0.05. Keyword : price fairness, handling complain, customer satisfaction and customer loyalty